The purpose of Life - Yasin, Shaykh Khalid; One Islam Productions (N.S.W, Australia : One Islam Productions, 2005)
Through the verses of the Holy Qur'an, Shaykh Khalid Yasin expounds upon the creation of the universe and this amazing world we live in, and how it came to be. With his logical style of argument, the Shaykh answers these questions with much wisdom
Title from title screen
Contains 3 parts of lectures. Part 1 (3 hrs. 11 min.), part 2 (2 hrs.), part 3 (1 hr. 45 min)
Presenter : Shaykh Khalid Yasin
DVD format
Keywords: Islam -- Customs and practices; Religious life -- Islam